Adjustment of mathematical models in the drying kinetics of grape residues cv. “Isabel” (Research, Society and Development, 2020)
This work aims to perform the drying kinetics of grape residues cv. “Isabel” at different drying air temperatures and adjust the experimental data obtained to the empirical mathematical models. The drying kinetics of grape residues (skins + seeds) were carried out in an air circulation oven with a speed of 1.5 m s-1, at temperatures of 50, 60 and 70 °C, where the samples were placed in trays stainless steel, up to constant weight. The empirical mathematical models of Handerson and Pabis, Lewis and Page were applied to the experimental data, in which the chi-square statistical indicators and determination coefficient R2 were evaluated. According to the determination coefficient (R2), the models presented values ​​above 0.93 for all applied temperatures, while analyzing the chi-square ( ) it can be observed that the Page model presented the lowest values. The highest rates of waste water removal occurred at the highest temperatures (70 °C) and the period of decreasing drying rate was only observed after 100 minutes of drying. As a suggestion for future work, it is possible to carry out a physical, physical-chemical and technological characterization of the dehydrated material and to evaluate the influence of the process temperatures on these parameters.